2023
DOI: 10.3390/fire6040155
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Experimental Fire on Physicochemical and Microbial Properties of a Mediterranean Cambisol

Abstract: Little is known about the bonfire impact on microbial properties in soil. This work aimed to study moderate- to high-severity experimental burning (250 °C) compared to unburned Cambisol in a natural Mediterranean environment (Croatia) on selected soil properties. The soil was sampled immediately and 1, 2, 4, and 6 months after the fire. The fire increased the mean weight diameter, water stable aggregates, and water repellence in different soil fractions, and the observed effect was the strongest immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, our work, although limited to the cultivable portion of the population, found that the predominant genera in these soils were Peribacillus or Bacillus , as is also reflected in the studies by Matos et al [ 92 ]. A recent study by Hrenović et al also showed these trends as well as an increase in phosphate binders in emerging communities [ 93 ]. In our study, we were able to verify that both this group and the potassium fixators were present; however, they had a smaller population and were less effective than the strains isolated from the sampling points not affected by fire.…”
Section: Discussionmentioning
confidence: 93%
“…However, our work, although limited to the cultivable portion of the population, found that the predominant genera in these soils were Peribacillus or Bacillus , as is also reflected in the studies by Matos et al [ 92 ]. A recent study by Hrenović et al also showed these trends as well as an increase in phosphate binders in emerging communities [ 93 ]. In our study, we were able to verify that both this group and the potassium fixators were present; however, they had a smaller population and were less effective than the strains isolated from the sampling points not affected by fire.…”
Section: Discussionmentioning
confidence: 93%
“…Climatic and biophysical characteristics of the Mediterranean (such as high temperatures during summer, the availability of fuel, i.e., dry vegetation) make the region fire-prone: naturally induced open fires have historically been present and helped form and shape the current landscape. However, population migration from rural to urban areas and the abandonment of agricultural lands, coupled with the effects of climate change, have resulted in the increased frequency and magnitude of fires [21]. In 2021, approximately 5000 km 2 of area was burned in the European Union [22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that fire can dramatically change the soil's chemical, physical, and biological properties, with subsequent effects on ecosystem dynamics [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%